Effect of natural environment on Hawrami clothing - Abdul, Dr. Hemn Baqir Abdul (Sulaimani Journal for Humanities, 2025)
Kurdish clothing is one of the items that can truly express the depth of Kurdish culture The national clothes of Hawramabad region have preserved their originality and main characteristics He hasn't lost it. This study is about the effect of natural environment on national men's clothing in Hawrmani region South Kurdistan The question is raised, what is the relationship between the national men's clothing in the Hawramabad region and in its natural environment? In other words, how the natural environment has affected the type, color and shape The size of each piece of Hawrami men's clothing is determined by the functional method The function of each piece of clothing in terms of responding to a natural environment. The most important findings of this study are that the men's national clothing of the region Hawramabad has a number of characteristics that are largely a response to the natural environment Different men's national clothes of Hawramabad region each have a specific function Suitable for adaptation to the natural environment of Hawramabad.